Women's Motivation on Politics in Malang Raya - Larasati, Atika Candra (Technium Social Sciences Journal, 2021)
Women have an important role in development, so the participation of women in politics is also needed. This is evidenced by several previous studies which reveal how the influence of women on government stability is more conducive to coruption action than the lack of women's participation in government. In addition, there is also an explanation related to the barometer of women's participation in politics in East Java which is considered mature. This also encourages researchers to use qualitative research methodologies with a phenomenological approach to look at the quality of women's motivations in politics. The location chosen is Malang Raya which is part of the province of East Java. Methods of data collection using interviews, documentation and observation. The results of the study show that women in addition to having rational and realistic motives for politics also have motivations that come from the family environment. Apart from self-actualization for the sake of emancipation, of course, women also have an impetus for regional development. The results of this study can be used as a reference for further research related to politics, sociology and women's studies